Social cohesion of the Malaysian Cul-de-sac neighborhoods: brief critical review of concepts / Anniz Fazli Ibrahim Bajunid, Mohamed Yusoff Abbas and Abdul Hadi Nawawi - Bajunid, Anniz Fazli Ibrahim; Abbas, Mohamed Yusoff; Nawawi, Abdul Hadi (Universiti Teknologi MARA Cawangan Selangor, 2018)
The national mass housing policies are currently being scrutinised on affordability and quality of life. The consideration of a better neighbourhood design is currently only evident in curvilinear and organic planning designs of neighbourhoods such as the cul-de-sac. The objective of this paper is to identify concepts of the cul-de-sac neighbourhoods and the community’s social cohesion through a critical review of available literature within the framework settings of a Malaysian pluralistic neighbourhood. The paper is anticipated to lead to methodological assessment processes of the physical environment and neighbourhoods as well as expand existing contextual knowledge of the Malaysian cul-de-sac neighbourhoods.